Interpretation, Construction and Revision of the Commercial Code: The Presumption of Holding in Due Course - Frederick K. Beutel (Washington University Law Quarterly, 1966)
It is usually assumed that the codification of the law or of a particular statute goes through four stages. These are drafting, enactment, interpretation, and revision. Due to a number of unusual circumstances, the history of the Uniform Commercial Code has not clearly followed these steps. So as a preliminary matter it might be beneficial briefly to review it.
Keywords: Commercial law; Statutes